Pushover Analysis Pile of ULA Jacket Platform Towards Earthquake Loads by SNI-1726:2012 - Dirta Marina Chamelia; Alim Bagus Prakoso; Silvianita Silvianita (DRPM (Direktorat Riset dan Pengabdian kepada Masyarakat) ITS, 2017)
This study aims at analyzing pushover on pile jacket structure based on SNI-1726:2012 standards for earthquake loads. Pushover analysis or ultimate strength was performed on ULA jacket platform operated by PHE ONWJ. The jacket platform is operated in the northwestern part of the Java Sea. Design of earthquake loads on ULA jacket platform structure with large seismic acceleration was obtained. From seismic analysis, dynamic response occurred on ULA jacket platform is evaluated, with natural structure period of 1.256 seconds. The largest shear base values were in X and Y directions resulted from seismic acceleration of PGA 0.2g. On member check, the critical part happens to be one of the members of WD2, and on joint check, the largest UC occurred on 401L joint, both were due to the aforementioned earth quake aceleration. Pushover analysis was then performed to obtain the value of RSR (Reserve Strength Ratio). The analysis yields an RSR value which far exceed the limiting criteria of API RP 2A WSD of RSR ≥ 0.8. Therefore it could be concluded that ULA jacket platform structure is within the range of low consequence category.